Mensagens e embustes: o deus Hermes no Hino Homérico e nas tragédias gregas As Traquínias, Hécuba e Troianas - Souza, Paulo Roberto Barbosa (2023)
This study explores the figure of Hermes, the messenger of the gods, focusing on his characteristics and functions, comparing them to those attributed to the herald and messenger figures, often indistinguishable, common in Athenian tragedy of the classical period. Emphasizing Hermes' traits from the Homeric Hymn to Hermes — industrious, deceitful, thief, herdsman, bearer of dreams, night watcher, gatekeeper, and messenger — particular attention is given to his role as trickster and/or deceiver. The analysis contrasts these attributes with the roles of heralds and messengers in Greek epic and drama, using the Hymn to Hermes as a benchmark. Specific attention is paid to the function and characteristics of heralds and/or messengers in the tragedies: Sophocles' "Trachiniae" and Euripides' "Trojan Women" and "Hecuba," focusing on characters like Lichas and Talthybius.